2020
DOI: 10.3390/ijms22010252
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial TSPO Deficiency Triggers Retrograde Signaling in MA-10 Mouse Tumor Leydig Cells

Abstract: The mitochondrial translocator protein (TSPO) has been shown to bind cholesterol with high affinity and is involved in mediating its availability for steroidogenesis. We recently reported that targeted Tspo gene deletion in MA-10 mouse tumor Leydig cells resulted in reduced cAMP-stimulated steroid formation and significant reduction in the mitochondrial membrane potential (ΔΨm) compared to control cells. We hypothesized that ΔΨm reduction in the absence of TSPO probably reflects the dysregulation and/or mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Accumulating evince indicates that the presence of TSPO participated the modulations of Ca 2+ homeostasis and mitochondrial fROS generation [10,11]. The deletion of TSPO gene provides to study the action of TSPO on the levels of apoptosis, ADPR, Mito-fROS and apoptosis via the stimulation of Ca 2+ permeable channels in the models of cell culture [40][41][42][43]. The stimulations of oxidative stress and ADPR induce the activation of TRPM2 in the ARPE19 [21,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evince indicates that the presence of TSPO participated the modulations of Ca 2+ homeostasis and mitochondrial fROS generation [10,11]. The deletion of TSPO gene provides to study the action of TSPO on the levels of apoptosis, ADPR, Mito-fROS and apoptosis via the stimulation of Ca 2+ permeable channels in the models of cell culture [40][41][42][43]. The stimulations of oxidative stress and ADPR induce the activation of TRPM2 in the ARPE19 [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…The influxes of Ca 2+ also action as a direct stimulus to cause TRPM2 stimulation-induced fROS in the ARPE19 [21,23]. The deletions of TSPO regulate mPTP activity via the inhibition of VDCC activation by decreasing the mitochondrial fROS generation, Ca 2+ influx and mitochondrial Ca 2+ accumulation in several cells [14,40]. PARP-1 can be overstimulated by fROS and PARP-1.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that derivatives 33 and 34, acting in vitro as good boron carriers, were able to concentrate boron atoms into tumor cells better than BPA. Despite its lower potency in comparison with 33, the fluoromethyl derivative 34 was selected for further in vivo studies owing to its lower cytotoxicity, the suitable boron uptake, and its potential as a 19 F magnetic resonance imaging (MRI) agent.…”
Section: Tspo-based Radioligands For Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…It also regulates the mitochondrial membrane potential, the respiratory chain, the immune response, the glial activation linked to brain damage, and finally it controls cell growth, differentiation , and programmed cell death . It was recently reported how TSPO controls nuclear gene expression by controlling intracellular signaling from the mitochondria to the nucleus, acting on the expression of several transcription factors . The programmed cell death control exerted by TSPO includes changes in TSPO expression levels and typically gives rise to reactive oxygen species (ROS) generation in mitochondria .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation